62 438
Assignments Done
99,4%
Successfully Done
In June 2018

Answer to Question #22227 in Algebra for Melanie amaya

Question #22227
2x - 3y = -1 | y = x - 1
Expert's answer
2x - 3y = -1
y = x& - 1

Substitute y=x-1 into the first equation:
2x-3(x-1)=-1
2x-3x+3=-1
-x=-1-3
x=4
Now we can find y=x-1=4-1=3

Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be first!

Leave a comment

Ask Your question

Submit
Privacy policy Terms and Conditions